The Impact of Safety Culture and Safety Behaviour towards Safety Performance: A Case Study of KTMB ETS Railway Maintenance Staff - Nor Aziati Abdul Hamid; Nur Azlin Suhaimi; Muhammad Hazim Ismail (Research in Management of Technology and Business, 2021)
A safety culture in general is an organizational culture that has a place in the high level of importance on safety beliefs, value, and attitudes. Poor safety performance in railway industry may increase the risk of accidents and threatened organization’s safety. However, the previous study that focuses on safety culture in context of Malaysian railway is still lacking. Therefore, this paper aims to determine the relationship among safety culture and safety behaviour on safety performance using a case study of KTMB ETS in the perspectives of railway maintenance, as well as identifying the key factor that effecting railway safety performance. A sample size of 43 workers involving the technicians and engineers at ETS Maintenance Depot Batu Gajah taken for this study through the distribution of online survey and purposive sampling was used. Several statistical analyses such as descriptive analysis, normality test, correlation test. The result showed that independent variables of safety culture have a significant positive relationship with safety behaviour which led to only one of three hypotheses was accepted. Maintenance and facility and equipment were the most influential factors towards Safety Performance with coefficient value of 0.487. The study findings can further enhance and contribute to have a better understanding of relationships that influences the railway maintenance to help KTMB figure out a better approach to improve in the future as well as help to make suggestion on how to enhance the safety issues and when designing and regulating the safety management system, several policies suggestions can be helpful for the decision makers of rail system’s operators and selected authorities.